An efficient solution of an integral equation applicable to simulation of propagation along irregular terrain. - Akorli, F.K.
An efficient algorithm is proposed as a substitute for the one originally used for the solution of an integral equation with applications to propagation studies. The results from the original and the proposed algorithms are compared by means of their application to the same terrain profile. A good overall agreement is displayed between the corresponding results from the two algorithms. Additionally, it is shown that considerable savings in processing time can be obtained with the proposed algorithm
Keywords: EM wave propagation; UHF frequency bands; Efficient algorithm; Efficient solution; Integral equation; Irregular terrain; Mobile telecommunication service; Processing time savings; Propagation simulation; Terrain profile